(untitled) (Eastern Medical College Journal, 2025)
Background: Thyroid dysfunction is widely reported to be more prevalent in patients with type 2 diabetes mellitus (T2DM) across different regions of the world; however, there is limited data available on this in our local context. The present study aimed to evaluate the thyroid dysfunction in patients with T2DM and find out the relationship with HbA1c. Materials and Methods: This cross-sectional study was carried out in Eastern Medical College Hospital from June 2024 to November 2024. Sixty (60) diagnosed type 2 diabetic patients and Sixty (60) nondiabetic people with the age range of 31 to 70 years were taken by convenience sampling. Permission for the study was taken from the IERB of EMC. Informed consent was obtained from each participant prior to sample collection. Patients with type 1 diabetes, gestational diabetes, thyroid cancer, thyroid surgery, renal and liver failure were excluded from the study. All the data was processed and analyzed using Microsoft Excel and IBM-SPSS v25.0. Results: The mean age was 48.55±8.6 years in the diabetic group and 42.41±9.8 years in the non-diabetic group). Serum TSH and FT3 were significantly higher in type 2 diabetic patients than those of non-diabetic people in this study. But there was no significant difference in serum FT4 between two groups. Among type 2 diabetic cases, 12 (20%) had thyroid dysfunction and in non-diabetics, 05 (8.2%) had thyroid dysfunction. Among cases 5 (8.3%) had hypothyroidism, 6 (10%) had subclinical hypothyroidism, 1 (1.6%) had hyperthyroidism. Among non-diabetic subjects 1 (1.6%) had hypothyroidism, 3 (5%) had subclinical hypothyroidism, 1 (1.6%) had hyperthyroidism. There was a positive significant correlation of HbA1c with TSH and FT3 but not with FT4 in the study cases. Conclusion: Diabetic complications and diabetes-related metabolic and demographic factors are related to abnormal thyroid hormone levels. Therefore, routine testing of thyroid hormones in diabetic patients is essential, as it can aid in the early detection of thyroid-related complications. Eastern Med Coll J. July 2025; 10 (1): 51-56